Cancer in Central and South America: Introduction. (September 2016) - Forman, David; Sierra, Monica S.
Highlights: Central and South American countries are undergoing sociodemographic and epidemiologic changes. The nature of health problems are transitioning from infectious to chronic diseases. Existing cancer incidence and mortality data are sparse due to limitations in information systems. Reliable statistics are needed to inform governmental entities responsible for cancer control. Results can be used to describe cancer risk factors in the region and develop control policies. Abstract: Central and South American countries (including Cuba) are experiencing rapid socio-demographic and epidemiologic changes and the nature of health problems are undergoing transition from infectious to chronic diseases, including cancer. Countries are poorly prepared to respond effectively to the subsequent challenges posed by the new patterns of disease. Existing data delineating the number of cancer cases and the distribution of cancer types from each country in the region are sparse due to limitations on health information systems for recording incidence and mortality despite improvements made in recent years. There is an urgent need for reliable statistics on cancer to inform governmental entities responsible for cancer control in the region. We attempted to obtain the best available cancer data from each country located in the region to provide an overview of current geographic patterns of cancer incidence and mortality in the 21st century.